Ovarian leiomyoma accompanied by a neglected abdominal wall leiomyoma: A case report and literature review - Jing Li; Mingxing Sui; Xiaodan Sun (Clinical Case Reports, 2024)
Key Clinical Message Ovarian leiomyoma and abdominal wall leiomyoma are both rare clinical entities. Here, we report the rare case with ovarian leiomyoma accompanied by a neglected abdominal wall leiomyoma to raise the awareness of clinicians of ovarian leiomyoma and multiple occurrences of benign leiomyoma for appropriate diagnosis.